Test the difference in the effectiveness of squeezing left leaves (Chromolaena odorata) and soursop leaves (Annona muricata L.) Against the Mortality of Hair Lice (Pediculus Humanus Capitis) - Anak Agung Ratih Eka Putri; Laksmyn Kadir; Tri Septian Maksum; Sarinah Basri K; Ayu Rofia Nurfadillah (Universitas Muhammadiyah Palu, 2026)
Vectors such as head lice (Pediculus humanus capitis) play a role as the cause of Pediculosis capitis which is still a public health problem. Therefore, effective control efforts are needed using safe natural materials such as kirinyuh leaves (Chromolaena odorata) and soursop leaves (Annona muricata L.) which contains active compounds that have the potential to be a hair lice killer. The purpose of this study is to distinguish the effectiveness of squeezing kirinyuh leaves and soursop leaves on hair lice mortality. The type of research uses a quasi-experimental design with a complete random design (RAL). The sample consisted of 190 adult stage head lice. Hair lice were given a pinch of kirinyuh leaves and soursop leaves with concentrations of 32%, 40%, and 48% with 3 repetitions and observed for 30 minutes. Data analysis was conducted using the ANOVA, Kruskal-Wallis and Mann-Whitney One-Way tests. The results showed that the highest mortality of head lice in left leaves was at a concentration of 48% of 90%, and the highest mortality of head lice in soursop leaves was at a concentration of 48% of 80%. In conclusion, there was no difference in the effectiveness of squeezing left leaves and soursop leaves on hair lice mortality (p-value = 0.100). The public is advised to use the juice of kirinyuh leaves and soursop leaves as environmentally friendly head lice control.